WHEN HEAVEN MEETS HELL: WILLIAM BLAKE AND ANDRÉ GIDE. (26th April 2015) - Pollard, Patrick
Abstract: This paper considers two related early twentieth-century French reactions to Blake's poetry and prose, specifically to The Marriage of Heaven and Hell . It analyses how André Gide discovered Blake through his reading of Charles Grolleau's translation (1900) and W. B. Yeats's prefaces first to his smaller edition in the Mermaid Series (1905) and then to his and E. J. Ellis's larger edition of Blake's Works, poetic symbolic and critical (1893) at some point before 1920. Attention is paid to the literary and critical background, including the opinions of Swinburne, together with the accounts published by Henry-D. Davray in the Mercure de France . Gide grouped Blake with several writers and thinkers, including Walt Whitman, Herman Melville, and Lautréamont, but it was above all when speaking of Dostoevsky that he emphasized the similarities which he believed he himself shared with the Russian novelist and Blake. The substantive points which are here elucidated are the simultaneous presence of Good and Evil within an individual's moral consciousness, and the need for constraint in the development of personal autonomy and power. The concept of a self divided between Satan and God is also shown to be present in his appreciation of R. L. Stevenson's The Strange Case of Dr Jekyll and Mr Hyde, and J. Hogg's The Private Memoirs and Confessions of a Justified Sinner . The analysis includes details of Gide's translation of Blake and a history of its publication by the Nouvelle Revue Française ( NRF ). The conclusion distinguishes Grolleau's mystical, Catholic approach to Blake from Gide's more nuanced appreciation of the presence of Satan and his positioning of the poet in a nonconformist pantheon which included Browning, Nietzsche, Goethe, and Dostoevsky.